2011
DOI: 10.1002/pola.24728
|View full text |Cite
|
Sign up to set email alerts
|

Samarium powder as catalyst for SET‐LRP of acrylonitrile in 1,1,1,3,3,3‐hexafluoro‐2‐propanol for control of molecular weight and tacticity

Abstract: Samarium powder was applied as a catalyst for single electron transfer‐living radical polymerization (SET‐LRP) of acrylonitrile (AN) in 1,1,1,3,3,3‐hexafluoro‐2‐propanol (HFIP) with 2‐bromopropionitrile as initiator and N,N,N′,N′‐tetramethylethylenediamine as ligand. First‐order kinetics of polymerization with respect to the monomer concentration, linear increase of the molecular weight with monomer conversion, and the highly syndiotactic polyacrylonitrile (PAN) obtained indicate that the SET‐LRP of AN could s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Single electron transfer-living radical polymerisation (SET-LRP) was reported by Percec and co-workers 94 and has significant benefits over traditional CRP methods, for example, only very small amounts of catalyst are required, and the polymerisation is very fast and leads to high molecular weight and low polydispersity. 95 The ability to control precisely molecular weight and tacticity is important because this greatly affects the physical properties of polymers such as toughness, thermal resistance and optical properties.…”
Section: D) Membrane Surfactant Proteinsmentioning
confidence: 99%
“…Single electron transfer-living radical polymerisation (SET-LRP) was reported by Percec and co-workers 94 and has significant benefits over traditional CRP methods, for example, only very small amounts of catalyst are required, and the polymerisation is very fast and leads to high molecular weight and low polydispersity. 95 The ability to control precisely molecular weight and tacticity is important because this greatly affects the physical properties of polymers such as toughness, thermal resistance and optical properties.…”
Section: D) Membrane Surfactant Proteinsmentioning
confidence: 99%
“…Recently, Percec, Haddleton, and co‐workers have demonstrated that Cu(0)‐mediated radical polymerization (SET‐LRP) displays near perfect bromide end‐group fidelity until relatively high conversion (typically 80%) for various monomers in polar solvents,14, 36–44 thus allowing precise synthesis of complex polymer architectures 24, 45–55. The AGET/ATRP technique in apolar solvents, developed by Matyjaszewski and coworkers,56, 57 enables significant reduction in the amount of metal catalyst used as well as marked improvement in end‐group fidelity (relative to direct ATRP; typically ∼87% end‐group fidelity at 90% monomer conversion) 31, 56, 57.…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all SET‐LRP studies inevitably introduced catalysts of Cu(0) into the polymerization system . Recently, our group have shown that SET‐LRP could be catalyzed by lanthanide metal such as Sm(0), Yb(0), and Gd(0) …”
Section: Introductionmentioning
confidence: 99%